2018
DOI: 10.1038/s41560-018-0116-1
|View full text |Cite|
|
Sign up to set email alerts
|

Implications of net energy-return-on-investment for a low-carbon energy transition

Abstract: Low-carbon energy transitions aim to stay within a carbon budget limiting potential climate change to 2 ºC-or well below-through substantial growth in renewable energy sources alongside improved energy efficiency and carbon capture and storage. Current scenarios tend to overlook their low net energy returns compared to existing fossil fuel infrastructure. Correcting from gross to net energy, we show that a low-carbon transition would likely lead to a 24 to 31% decline in net energy per capita by 2050, implying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 36 publications
4
65
1
1
Order By: Relevance
“…A 2006 CCS and sRE life cycle comparison in the German context did not evaluate net-energy performance but found that, on a lifecycle basis, CCS emissions are considerably greater compared to off-shore wind farms in the North Sea and concentrated solar power (CSP) plants in North Africa per unit of energy delivered 19 . Nevertheless, there are limited studies discussing the EROEI of CCS 20 or comparing the net energy performance of CCS and sRE.…”
Section: Introductionmentioning
confidence: 99%
“…A 2006 CCS and sRE life cycle comparison in the German context did not evaluate net-energy performance but found that, on a lifecycle basis, CCS emissions are considerably greater compared to off-shore wind farms in the North Sea and concentrated solar power (CSP) plants in North Africa per unit of energy delivered 19 . Nevertheless, there are limited studies discussing the EROEI of CCS 20 or comparing the net energy performance of CCS and sRE.…”
Section: Introductionmentioning
confidence: 99%
“…One typical finding is that fossil fuels have a relatively high EROI which gradually declines over time, while renewable technologies usually have lower EROIs 68 . This poses substantial challenges for a low-carbon transition because it implies reductions in useful energy 69 .…”
Section: Multi-scale Integrated Analysis Of Societal and Ecosystem Mementioning
confidence: 99%
“…The energy penalty in suitably optimised plants, would probably only be of the order of 25%, but because very few existing plants are so optimised, the energy costs for CCS could be appreciably higher. This energy cost will further lower their EROI [20,21]. Other forms of mechanical CDR include negative emissions technologies (NETs) such as direct air capture of CO 2 or enhanced weathering of minerals.…”
Section: Why Do We Need Re?mentioning
confidence: 99%
“…The claims for PV cells vary from PV still being an energy sink to PV cells paying back their energy costs in a few days. Some researchers have suggested that actual EROI values for RE are lower than 11, and in some cases even lower than 3.0, especially if storage energy costs are incurred [20,81]. The EROI values discussed here are assumed to be the "standard" EROI [21].…”
Section: Technical Potential For Other Re Sourcesmentioning
confidence: 99%
See 1 more Smart Citation